2011
DOI: 10.1158/1078-0432.ccr-10-2804
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Deprivation Boosts Prostatic Infiltration of Cytotoxic and Regulatory T Lymphocytes and Has No Effect on Disease-Free Survival in Prostate Cancer Patients

Abstract: Purpose: The value of neoadjuvant hormone therapy (NHT) prior to radical prostatectomy as a means of restraining prostate cancer (PCa) and strengthening its immunotherapy is still uncertain. This article asks whether it subverts immunoregulatory pathways governing tumor microenvironments, and has an impact on patient outcome.Experimental Design: We microdissected epithelium and stroma from cancerous and normal prostate specimens from 126 prostatectomized patients, of whom 76 had received NHT, to detect cytokin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 49 publications
4
62
0
1
Order By: Relevance
“…This effect is in stark contrast to the frequent observation of AR reactivation in castration-resistant prostate cancer; which is often concomitant with the overexpression of de novo steroidogenic enzymes [9]. Upregulated genes in NHT tumors were linked to growth suppression and increased apoptosis (for example, DUSP2, DUSP4, CCDC8, TNS4) and also with cytotoxic T lymphocytes (for example, CD8A, GZMK), with the latter in line with previous reports demonstrating an increase in prostatic infiltration of lymphocytes post-hormone treatment [10,11]. However, although the data suggested that most tumors were responding to androgen deprivation therapy at the time of tumor collection, four tumors displayed elevated CHGA expression at the mRNA level ( Figure 1D).…”
Section: Evidence Of Therapy Response and Resistance In Neoadjuvant Tsupporting
confidence: 87%
“…This effect is in stark contrast to the frequent observation of AR reactivation in castration-resistant prostate cancer; which is often concomitant with the overexpression of de novo steroidogenic enzymes [9]. Upregulated genes in NHT tumors were linked to growth suppression and increased apoptosis (for example, DUSP2, DUSP4, CCDC8, TNS4) and also with cytotoxic T lymphocytes (for example, CD8A, GZMK), with the latter in line with previous reports demonstrating an increase in prostatic infiltration of lymphocytes post-hormone treatment [10,11]. However, although the data suggested that most tumors were responding to androgen deprivation therapy at the time of tumor collection, four tumors displayed elevated CHGA expression at the mRNA level ( Figure 1D).…”
Section: Evidence Of Therapy Response and Resistance In Neoadjuvant Tsupporting
confidence: 87%
“…In prostate cancer, however, the prognostic value of tumor-infiltrating lymphocytes has long been unclear. Earlier studies reported that prostate tumor-infiltrating lymphocytes were either not associated with prognosis or associated with better outcomes (8)(9)(10). Recent studies in large cohorts have however challenged this notion.…”
Section: Discussionmentioning
confidence: 99%
“…Because androgen ablation is associated with an increased production of TGFb in the prostate, CD73 may also be induced by androgen deprivation therapy (ADT). This possibility merits further investigation, especially considering that ADT is known to increase prostatic T-cell infiltration without affecting clinical outcomes (46)(47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For immunohistochemistry (IHC), formalin-fixed, paraffin-embedded sections were treated with H 2 O 2 /3% for 5 minutes to inhibit endogenous peroxidase and then washed (24).…”
Section: Immunohistochemistrymentioning
confidence: 99%